2022
DOI: 10.31004/basicedu.v6i4.3097
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kemampuan Literasi Peserta Didik Sekolah Dasar dalam Menyelesaikan Soal Asesmen Kompetensi Minimum

Abstract: Membaca merupakan keahlian yang harus dimiliki oleh setiap individu manusia dan diajarkan dari sejak dini. Setiap peserta didik memiliki tingkat kemampuan membaca yang berbeda-beda, AKM dapat digunakan untuk mengevaluasi peserta didik dalam kemampuan membaca. Oleh karena itu, tujuan dilakukan penelitian untuk mengetahui kemampuan literasi membaca pada peserta didik kelas V, mengetahui faktor yang mempengaruhi kemampuan literasi dan cara peserta didik kelas V dalam menyelesaikan soal literasi AKM. Pada peneliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
6
0
4
Order By: Relevance
“…If educators already have good understanding and knowledge, it is hoped that later students will also have good understanding. Apart from that, by attending workshops related to AKM, it is hoped that teachers will be more thorough in developing AKM reading literacy components, and the forms of AKM questions used can Hari Sugiharto Setyaedhi / Workshop for Preparation of Minimum Competence Assessment for Private High School Teachers be more varied (Lengkanawati et al, 2023;B. Maharani & Wahidin, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If educators already have good understanding and knowledge, it is hoped that later students will also have good understanding. Apart from that, by attending workshops related to AKM, it is hoped that teachers will be more thorough in developing AKM reading literacy components, and the forms of AKM questions used can Hari Sugiharto Setyaedhi / Workshop for Preparation of Minimum Competence Assessment for Private High School Teachers be more varied (Lengkanawati et al, 2023;B. Maharani & Wahidin, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…National numeracy literacy ability data obtained shows that student literacy is currently relatively low. The low numeracy literacy results are caused by students experiencing several difficulties that become obstacles for them in using various kinds of numbers and symbols related to basic mathematics, solving problems in various contexts of daily life, analyzing information displayed in various forms such as graphs, pictures, tables, diagrams, charts, and so on, and having difficulty interpreting analysis results to predict and make decisions (Ahmad et al, 2021;Anggraini & Setianingsih, 2022;B. Maharani & Wahidin, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Hal tersebut menunjukkan adanya kesulitan siswa memilih jawaban yang benar pada aspek mengevaluasi. (Maharani & Wahidin, 2022) asesmen yang diujikan hanya terbatas pada siswa yang menanggapi pertanyaan dari setiap soal yang telah disiapkan.…”
Section: Gambar 5 Kemampuan Literasi Membaca Siswa Pada Aspek Mengeva...unclassified
“…Investigating educators' knowledge and readiness is a primary focus of a few of these research studies. Students with logical-mathematical and visual-spatial forms of verbal linguistics intelligence may solve the mathematical problems in the AKM questions, according to research by Wardani et al (2020). Sari et al (2021) found that just 17.65% of students were able to complete numeracy issues.…”
Section: Introductionmentioning
confidence: 99%